Establishment of a Transient and Stable Transfection System for Babesia duncani Using a Homologous Recombination Strategy - Wang, Sen; Li, Dongfang; Chen, Fangwei; Jiang, Weijun; Luo, Wanxin; Zhu, Guan; Zhao, Junlong; He, Lan (Frontiers in Cellular and Infection Microbiology, 2022)
Babesia duncani is a pathogen causing human babesiosis, which is widespread in North America. Genetic modification provided an invaluable molecular tool to dissect the biology and pathogenesis of pathogens. However, the tool of genetic modification for B. duncani has not been reported. Developing genetic manipulation methods is necessary to improve strategies for studying and understanding the biology of protozoan pathogens. For the establishment of genetic modification methods, promoters, selectable marker and reporter genes are essential. Here, the double-copy gene elongation factor-1α (ef-1α) and it’s promoters were amplified by conventional PCR, and confirmed by sequencing. We established the transient transfection method by using ef-1αB promoter and the reporter gene mCherry. Stable transfection was achieved through homologous recombination to integrate selection marker hDHFR-eGFP into the parasite genome. After that, we tested the potential of this genetic modification method by knocking out the thioredoxin peroxidase-1 (TPX-1) gene. The results showed that under the drug pressure of 5 nM WR99210, we observed the parasites expressing green fluorescence (eGFP) by flow cytometry in 7 days after electroporation, the proportion of parasites expressing green fluorescent protein under drug pressure reached 96.3%. Subsequently, the clone line of TPX-1 knockout parasite was successfully obtained by the limiting dilution method. All in all, we provide a transfection method for B. duncani. This method would speed up gene function research and vaccine development of B. duncani.